2000
DOI: 10.2135/cropsci2000.401226x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Elite Sorghum Inbred Lines Assessed with Simple Sequence Repeats

Abstract: phisms among 36 sorghum lines were equally low for profiles obtained by means of 30 RAPD primers or 29 DNA markers are being increasingly utilized in cultivar develop- RFLP probes. Vierling et al. (1994) found 73 RAPD ment, quality control of seed production, measurement of genetic diversity for conservation management, varietal identity, and to assist primers discriminated among sorghum lines but those in maintenance of intellectual property protection (IPP). The use of data did not allow lines to be associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
97
5
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 22 publications
(34 reference statements)
22
97
5
1
Order By: Relevance
“…The polymorphism values reported in this study were higher than those reported by Ganapathy et al (2012). In general, the current results concur with the results of Smith et al (2000) and Geleta et al (2006), who also showed that markers with moderate PIC values can classify most of the inbred lines and detect the polymorphism rate at a specific locus (Smith et al, 2000). The morphological traits of ear-head shape, compactness and orientation played a vital role in the delineation of the diversity into different groups.…”
Section: Discussionsupporting
confidence: 91%
“…The polymorphism values reported in this study were higher than those reported by Ganapathy et al (2012). In general, the current results concur with the results of Smith et al (2000) and Geleta et al (2006), who also showed that markers with moderate PIC values can classify most of the inbred lines and detect the polymorphism rate at a specific locus (Smith et al, 2000). The morphological traits of ear-head shape, compactness and orientation played a vital role in the delineation of the diversity into different groups.…”
Section: Discussionsupporting
confidence: 91%
“…9, most of the lines from ICRISAT (I line) were selected for resistance to leaf diseases, early vigor, stay-greenness, high yield, and Al tolerance and showed a difference in genetic background from lines from Japan (J line) or improved lines (JU line). Smith et al (2000) reported that SSR data was in agreement with the pedigree information or per formance information.…”
Section: Genetic Diversity Of Sorghum Germplasmmentioning
confidence: 67%
“…Simple sequence repeats (SSR) markers are useful indices for studying the genetic diversity of the world sorghum germplasm lines, and were used for the study of Eritrean sorghum landraces, the elite sorghum inbred lines and the sorghum from Southern Africa (Dje et al, 2000;Ghebru et al, 2002;Smith, et al, 2000;Uptmoor et al, 2003); genetic redundancy in the 'Orange' sorghum (Dean et al, 1999); and mapping of sorghum genome (Bowers et al, 2003;Menz et al, 2002). SSR fi ngerprints are generally highly discriminative and are often used to distinguish varieties, or even individuals, and reveal parentage and identity (Karp et al, 1996) and grouping the maize germplasm based on heterotic groups (Reif et al, 2003).…”
mentioning
confidence: 99%
“…Also, differences in PIC values may be due to the polymorphism of the SSR markers used and genetic differences among the South African dessert watermelon landraces. The PIC values of loci provide an estimate of the discriminatory power of loci, considering the number of alleles and their relative frequencies (Smith et al, 2000). In this study, over 80% of the SSR-loci in this study had PIC value of > 0.65, indicating an adequate discriminatory power of individual SSR loci used in the study.…”
Section: Discussionmentioning
confidence: 59%